Three woven structures of reduced graphene oxide conductive silk fabrics prepared by two different methods for electrical setting and sensing. (30th November 2022) - Chen, Kun; Xu, Jingying; Zheng, Yiqian; Li, Jialin; Hong, Xinghua
Silk is widely used in flexible electronic equipment and intelligent textiles because of its well mechanical properties and bio-compatibility. Reduced graphene oxide is a two-dimensional carbon material with honeycomb lattice structure atoms and excellent electrical conductivity, which can give fabric a significant electrical conductivity. Herein, three types of RGO/Silk woven fabrics (satin, twill, and backed weaves) and two coating methods (screen printing and impregnating) were provided to explore the electrical properties, pressure sensing property and influence mechanism of silk surface characteristics. The results show the best preparation process of these two methods is five finishing times and 2 h reduction time. And the RGO/silk fabrics obtained by screen printing and impregnation have similar resistivity, but the RGO/silk fabrics obtained by screen printing provide better washing resistance. After nine washing cycles, the resistance of RGO/silk fabrics prepared by screen printing is 2 kΩ less than that obtained by impregnation. In addition, under the two methods, backed weave fabric shows the best conductivity, followed by twill and satin weave. Moreover, the RGO/Silk fabric sensor responds well to human motion, like finger bending and hand-holding objects. This work provides a train of thought and method for flexible conductive silk fabric.